2021
DOI: 10.3390/app11094114
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of Wound Dressings with Bioactive Agents to Achieve Improved Pro-Healing Properties

Abstract: The great variety of wounds and the lack of an effective universal treatment method has resulted in high demand for modern treatment strategies. Traditional approaches are often ineffective on a variety of chronic wounds, such as venous ulcers or the diabetic foot ulcer. There is strong evidence that naturally derived bioactive compounds have pro-healing properties, raising a great interest in their potential use for wound healing. Plant-derived compounds, such as curcumin and essential oils, are widely used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 88 publications
0
32
0
Order By: Relevance
“…Composite dressings can contain natural products for delivery or be composed of a natural product itself [ 121 ]. An example of such a dressing was created by Gao et al, who used chitosan and diazo resin to create a hydrogel composite dressing [ 27 ].…”
Section: Advanced Delivery Strategies For Natural Wound-healing Compo...mentioning
confidence: 99%
“…Composite dressings can contain natural products for delivery or be composed of a natural product itself [ 121 ]. An example of such a dressing was created by Gao et al, who used chitosan and diazo resin to create a hydrogel composite dressing [ 27 ].…”
Section: Advanced Delivery Strategies For Natural Wound-healing Compo...mentioning
confidence: 99%
“…This leads to an imbalance between the regulatory molecules involved in healing and thus hinders wound healing. It is also considered to be the most common factor affecting the deterioration of acute wounds into chronic wounds [292]. Some MPs, such as CS, have good antibacterial properties under acidic conditions.…”
Section: Development Of Activities-enhanced Mps Wound Dressingsmentioning
confidence: 99%
“…Natural antimicrobial agents have shown the advantage of high biosafety. Honey, essential oils, tannins, active amino acids and peptides, hesperidin, etc., have been widely used in recent years [65,292,[307][308][309]. Some studies reported that the addition of Manuka honey to MPs dressings showed good antibacterial activity against Staphylococcus aureus, Streptococcus pyogenes, Acinetobacter baumannii, Pseudomonas aeruginosa and Proteus mirabilis [248,310].…”
Section: Development Of Activities-enhanced Mps Wound Dressingsmentioning
confidence: 99%
“…When a patient is unable to move, pressure ulcers may appear. Such a case was also healed after several dressings were applied, including a honey-loaded alginatebased product, named Algivon ® [131,132]. An improved version of this dressing, Algivon ® Plus, showed good clinical results when applied on chronic wounds [133].…”
Section: Commercially Available Pharmaceutical Alginate-based Productsmentioning
confidence: 99%